Coexistence of bullous pemphigoid with neuropsychiatric comorbidities is associated with anti‐BP230 seropositivity. (21st May 2021) - Ständer, S.; Hammers, C.M.; Vorobyev, A.; Schmidt, E.; Hundt, J.E.; Sadik, C.D.; Lange, T.; Zillikens, D.; Ludwig, R.J.; Kridin, K.
Abstract: Background: While clustering of bullous pemphigoid (BP) with neuropsychiatric diseases is well‐established, the clinical and immunological profile of BP patients with this comorbidity remains to be decisively determined. Objectives: To evaluate the burden of neurological and psychiatric comorbidities among patients with BP and to elucidate the clinical, immunological and immunopathological features of patients with BP and comorbid neuropsychiatric conditions. Methods: We performed a retrospective study encompassing patients diagnosed with BP throughout the years 2009–2020 in a specialized tertiary referral centre. Multivariate logistic regression model was used to identify predictors of neuropsychiatric conditions among patients with BP. Results: The study included 273 patients with BP, of whom 123 (45.1%) presented with comorbid neuropsychiatric disease. Compared to the remaining patients with BP ( n  = 150), those with pre‐existing neuropsychiatric diseases demonstrated older mean [standard deviation (SD)] age [81.7 (9.1) vs. 76.9 (10.1); P  < 0.001], female preponderance (65.0% vs. 49.3%; P  = 0.009), higher seropositivity rate of anti‐BP230 (67.7% vs. 36.5%; P  = 0.006) and higher levels of anti‐BP180 NC16A IgG [651.3 (1279.6) vs. 370.4 (818.6) U/mL; P  = 0.039]. In multivariate analysis, anti‐BP230 seropositivity was independently associated with coexistence of BP with neuropsychiatric conditions [adjusted odds ratio (OR), 3.43; 95% CI, 1.24–9.52; P  = 0.018]. In a sensitivity analysis confined to patients with neurological diseases ( n  = 103), older age [82.1 (8.4) vs. 77.2 (10.3); P  < 0.001] and increased anti‐BP230 seropositivity (68.0% vs. 39.7%; P  = 0.018) were identified. Conclusions: The coexistence of BP with neuropsychiatric diseases is independently associated with the generation of anti‐BP230 antibodies.